A survey of various ecosystems in relation to habitat conservation and urban biodiversity in Mati City, Davao Oriental, Philippines - Edison Macusi; Rancil Quin Salang; Jireh Rosales (Davao Research Journal)
In ecology, the community structure of an ecosystem is paramount to demonstrating the integrity and interrelationship of the various flora and fauna of the ecosystem. The objectives of this paper are to show the variation of community structures from a microecosystem (log ecosystem) to a macroecosystem (mangrove forests and seagrass beds) and determine the biodiversity of these ecosystems. In this paper, class data gathered from the field were quantified to produce a coherent result showing that the ecosystem in a typical Philippine college or university can be used as a field laboratory to study biodiversity and increase the awareness of students and the academic community on understanding the various concepts of ecology. The relative abundance, rank abundance, Simpson and Shannon-Wiener biodiversity indices were measured and quantified for the various ecosystems. Furthermore, the apparent lack of concern for biodiversity is discussed, as is how these fragmented ecosystems are being neglected because of a lack of coherent policy to address these issues and protect the ecosystem landscape.